The Role of The Digital Economy in Electronic Commerce - To’rayev Xurshid Baxriddin o’g’li; Kasimov Azamat Abdukarimovich (European Science Publishing, 2024)
This article will tell you about e-commerce. That is, information is given about what e-commerce is, how e-commerce works, about types of e- commerce, about mobile electron Commerce and about the advantages and disadvantages of e-commerce.
Keywords: e-commerce, e-trade, internet, mobile e- commerce, business.